Overcoming polarity: Franz Spunda’s Devachan and the birth of the “new race” - Domínguez Márquez, Guadalupe Antonia (2024)
The Austrian writer Franz Spunda published a series of occult novels during the decade of the twenties, which have received very little academic attention. Through the application of methodological tools from the field of Western Esotericism Studies, this paper presents a critical analysis of his first novel, Devachan, in whose thematic contents, an alignment with, but also a deviation from modern Theosophy’s doctrinal axis, becomes noticeable. The Spundian desire to overcome all polarity and the justification of transgressive means to achieve this end, constitutes the breaking point with Theosophy and  the embracing of an extreme form of alchemy.